A mommy for Easter - Goodnight, Linda (Love inspired., 2024)
"She'd do anything to be a mother...But is she ready to face the past? Back in his hometown after a decade, Jake Colter and his adorable toddler are a reminder of everything Rachel Hamby lost. And working on the same Easter committee with her ex-husband makes avoidance impossible. Throw in a small town's matchmaking scheme and Jake's sweet dog, and soon Rachel's falling for the little girl...and her father. But will Rachel risk a second chance with the painful secret she's keeping?"